ANALISIS DRAMATURGI ERVING GOFFMAN DALAM IMPLEMENTASI SEKOLAH RAMAH ANAK DI SMA NEGERI 1 SURAKARTA - Prihandoyo, Muhammad Dimas; Liestyasari, Siany Indria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the front stage and backstage impression management of the implementation of the Child-Friendly School Program that has been implemented in SMA Negeri 1 Surakarta. The research data were obtained from SMA Negeri 1 Surakarta. This study uses a descriptive approach and qualitative research type. The data used are primary data and secondary data. Primary data were obtained from in-depth observations and interviews, while secondary data were obtained from the results of analyzing various journals and child-friendly school guidelines. The results of the study indicate that in implementing child-friendly schools there are various formulas that schools use to implement child-friendly schools properly. The results of the analysis of front stage and backstage impression management show that schools are able to give a good impression to outsiders, but there are many shortcomings in implementing the child-friendly school program. The child-friendly school program is also no longer an important concern for the government or schools.